2019
DOI: 10.1016/j.eclinm.2019.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Consistent, Excess Viral Meningitis Incidence Rates in Young Males: A Multi-country, Multi-year, Meta-analysis of National Data. The Importance of Sex as a Biological Variable

Abstract: Background: Sex can be an important biological variable in the immune response to infections and the response to vaccines. The magnitude and consistency in age-specific sex differences in the incidence of viral infections remain unclear. Methods: We obtained data from national official agencies on cases of viral meningitis by sex and age group over a period of 6-16 years from five countries: Canada, Czech Republic, Germany, Israel, and Poland. Male to female incidence rate ratios (RR) were computed for each ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 41 publications
0
27
1
1
Order By: Relevance
“…The meta-regression results revealed that among the variables, age group contributed almost all the variation in the incidence RRs. The results of this study contrast with the perception that males suffer more than females from infectious diseases [13,31].…”
Section: Discussioncontrasting
confidence: 99%
“…The meta-regression results revealed that among the variables, age group contributed almost all the variation in the incidence RRs. The results of this study contrast with the perception that males suffer more than females from infectious diseases [13,31].…”
Section: Discussioncontrasting
confidence: 99%
“…Our ndings considerably extend those from population-based studies in multiple or single countries (10)(11)(12) and provide age-speci c pooled estimates of the male to female IRR, while controlling for country and different timeperiods. We have used the same meta-analytic methods to combine data from various countries and time periods for other diseases and demonstrated a male predominance in viral meningitis and shigellosis in young children (13,14). On the other hand, the incidence rates for pertussis were higher in females at all ages (29).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings considerably extend those from population-based studies in multiple or single countries (9,10,25,26), by producing age-specific pooled estimates of the incidence rate ratio accounting for country and time-period. A male predominance has been reported in the incidence of certain other infectious diseases, mainly in children (27,28).…”
Section: Discussionmentioning
confidence: 99%